Knowledge, Attitude, and Practices (KAP) Survey Towards Pelvic Floor Muscle Training (PFMT) Among Pregnant Women - Temtanakitpaisan T; Bunyavejchevin S; Buppasiri P; Chongsomchai C (Dove Medical Press, 2020)
Teerayut Temtanakitpaisan,1 Suvit Bunyavejchevin,2 Pranom Buppasiri,1 Chompilas Chongsomchai1 1Department of Obstetrics and Gynecology, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand; 2Department of Obstetrics and Gynecology, Faculty of Medicine, Chulalongkorn University, Bangkok, ThailandCorrespondence: Teerayut TemtanakitpaisanDepartment of Obstetrics and Gynecology, Faculty of Medicine, Khon Kaen University, Khon Kaen, ThailandTel +66819656423Email jacktemtanakitpaisan@hotmail.comObjective: To assess knowledge, attitude, and practices (KAP) of pelvic floor muscle training (PFMT) among Thai pregnant women.Patients and Methods: One hundred and ten Thai pregnant women who attended the antenatal clinic of a tertiary care hospital were recruited. They were classified as “aware” if they could recognize PFMT. Questionnaires regarding the participants’ attitudes and practice toward PFMT were subsequently collected from “aware” group.Results: The mean ±SD of age and gestational age were 30.5 ± 5.4 years and 20.8 ± 10.8 weeks, respectively. Sixty-one participants (55.5%) recognized PFMT, but only seventeen (27.9%) correctly answered all of the questions, which is classified as perceptive. There was no association between their educational level and PFMT knowledge (p = 0.63). Most of them (98.4%) understood that PFMT can be performed during pregnancy and believed that PFMT did not affect the pregnancy outcomes. However, only 10.7% of the aware women performed PFMT irregularly during pregnancy.Conclusion: Half of the pregnant women in this study were aware of PFMT. The majority of women felt that PFMT had positive effects on their health, emotions, sex, and quality of life. Education concerning PFMT and motivation to maintain the adherence of practicing the exercises are required.Keywords: KAP, pelvic floor muscle training, pregnant women